Customer Perceived Service Quality, Product Quality, Satisfaction and Loyalty in Beauty Business - Restiana, Lisa (IPTEK Journal of Proceedings Series, 2020)
In the hyper competitive and low entry barrier in beauty industry, customer loyalty is critical factor for gaining success for the company. The customer loyalty and satisfaction are key of success factor for strengthen bussiness performance. By creating and preserving customer loyalty, business entities can develop a long term relationship with the customers. The purpose of the research is to know further the determinant of customer satisfaction and loyalty from service quality and product quality. This study is designed by qualitative research by using theoretical review based and supporting by previously research. The basic concepts underlyed this theoretical review are dimensions of service quality, product quality, customer satisfaction, and customer loyalty. By critical review and classifying the result of previous research, this research found some propositions: (1) Service quality have significant effect on customer satisfaction (2) Product quality have significant effect on customer satisfaction (3) Service quality have significant effect on customer loyalty (4) Product quality have significant effect on customer loyalty (5) customer satisfaction have significant effect on customer loyalty.